IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AT THE BACKDOOR LISTING PROSEDUR AS MEANS OF BUSINESS DEVELOPMENT IN INDONESIA STOCK MARKET - Muryanto, Yudho Taruno; Wulandari, Anisa Dwi (Yustisia, 2016)
AbstractDevelopments in the field of capital markets encourage the emergence of various corporate actions to obtain benefits such as a public company. One of the emerging corporate actions which have been done is Backdoor Listing. Regulations in the capital market is generally allowed backdoor listing. Backdoor Listing procedure are often executed in Indonesia are as follows: (1) The acquisition of control of a public company by private company through the rights issue (2) the acquisition of private company by an public company that has an affiliate relationship with the private company into standby purchaser/ new controllers. Study fulfillment of the Good Corporate Governance principles in the backdoor listing procedure is known that this procedure is still not met the Principles of Transparency, Accountability, as well as fairness and equity. It is needed to establish the rules of providing transparency obligation to assess the feasibility of a new public company controller.